ER SØKING I GOOGLE NOK? PH.D.-KURS VED NTNU UNIVERSITETSBIBLIOTEKET – EN UTVIKLINGSHISTORIE - Faber, Hege Charlotte; Taylor, Solveig Isabel (Nordic Journal of Information Literacy in Higher Education, 2011)
<!--[if gte mso 9]> 800x600 <![endif]--><!--[if gte mso 9]> Normal 0 21 false false false NO-BOK X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]--> This paper presents an overview of how the university library at the Norwegian University of Science and Technology (NTNU) participates in the education and support of Ph.D. candidates. NTNU has a broad academic scope, the range of subjects are from engineering and technology to humanities, psychology, medicine and fine arts. The courses given by the NTNU university library reflects the different cultures, traditions, contents and developments. This paper also discusses various aspects in connection with the need for information literacy at doctoral level, integration of the courses as well as the need for further development in this field which is both connected to technological developments (such as Google) as well as implementation of the Norwegian Qualification Framework.